Complete Hypersurfaces with Constant Scalar Curvature in a Special Kind of Locally Symmetric Manifold (Analysis in Theory and Applications, 2012)
In this paper, we investigate $n$-dimensional complete and orientable hypersurfaces $M^n$ $(n ≥3)$ with constant normalized scalar curvature in a locally symmetric manifold. Two rigidity theorems are obtained for these hypersurfaces.
Keywords: hypersurfaces; scalar curvture; locally symmetric manifold.